Postgraduate Training on Research Tools & Techniques, Department of Biochemistry, Ziauddin University - Saeeda Baig; Shamim Mushtaq (ziauddin University, 2024)
Introduction: Hands-on postgraduate training on techniques are the foundation of professional development in research. The medical professionals generally show resistance towards learning laboratory techniques especially related to molecular biology. A hands-on workshop was designed for post graduate candidates, to overcome their inhibitions and develop proficiency at research based molecular techniques. Key Words: Postgraduate Training, Biomedical Research, Medical Education.